(untitled) (Marketing Journal, 2025)
This article analyzes the factors that influence the labor productivity of an organizationʼs management system. It outlines the main aspects of effective management principles, including strategic planning, motivation, the implementation of innovative tech nologies, organizational culture, and the efficient use of resources. The article also examines the impact of both internal and external factors on organizational performance.